INITIAL TEACHER EDUCATION IN ROMANIA - OVERCOMING OR SUCCUMBING TO PAST WEAKNESSES AND THREATS? - Oana-Rica POPA; Norica-Felicia BUCUR (Challenges of the Knowledge Society)
In the light of the new Education Act dedicated to preuniversity education that came into force in Romania in 2023, prospective teachers are to be offered two alternative pathways to enter their profession: a twelvemonth or eighteen-month master’s degree. Timewise, those determined to embrace the teaching career will have to comply with these provisions starting with the 2027-2028 school year. Considering these specific regulations belonging to the recent legal framework governing education in Romania, our paper aims at investigating the advantages and disadvantages of the options given to future teachers, so as to tentatively predict whether past obstacles might be overcome. By briefly outlining both the tendencies and realities of initial teacher education at international and European levels and by presenting the evolution of initial teacher education in Romania in the post-communist era, we lay the basis for our small-scale investigation. The responses of our interviewees (school inspectors, school principals, experienced teachers, academics) point not only to the imminent threats and inherent weaknesses, but also to the long-term prospects of this educational reform, as professionalising the teaching industry advances the profession as a whole and goes a long way to create better opportunities for student success.